Headline Politik Dan Politik Headline Pada Harian Fajar Dan Tribun Timur - Riza Darma Putra; Muhammad Zaenal; Titien Yusnita (Jurnal Komunikasi Pembangunan, 2016)
RIZA DARMA PUTRA. Headline Headline Politics and Politics in the Daily Dawn and East Tribune (study of local politics and media relations in Makassar) This study aims to determine (1) The reasons political news serve as a headline by Dawn and East Tribune, (2) Trends news headlines politics Dawn and East Tribune, (3) Policy editor of Dawn and East Tribune in determining headline politics and the latter view factor which affect the determination of the political headlines and political relationship with the local South Sulawesi. This study combines quantitative and qualitative approaches. The author uses content analysis to see the trend of media while qualitative mengeskplor editorial policy and the factors that influence the political headlines. These results indicate reasons for choosing politics as headlines for news value but it is also due to demand by readers. Daily headline news tendency Dawn and Eastern Tribune is more directed to politics as an arena of power struggle. Factors affecting the determination of the political headlines are internal factors that editorial policy as well as in the specific context of capital owners. While external factors to the interests of the local political elite South Sulawesi.Keywords: political economy, political headlines, media, local politics